Urinary fluoride excretion in children exposed to fluoride toothpaste and to different water fluoride levels in a tropical area of Brazil - Forte, Franklin Delano Soares [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Sampaio, Fábio Correia [UNESP] (FapUNIFESP (SciELO), 2008)
The aim of this study was to evaluate the urinary fluoride excretion of 2- to 7-year-old children exposed to different water fluoride concentrations in the city of Catolé do Rocha, PB, Brazil. Forty-two children were allocated to 3 groups according to the concentration of fluoride in the water: G1 (n=10; 0.5-1.0 ppm F), G2 (n=17; 1.1-1.5 ppm F) and G3 (n= 15; >1.51 ppm F). The study was carried out in two 1-week phases with 1-month interval between the moments of data collection: in the first phase, the children used a fluoride toothpaste (FT) (1,510 ppm F) for 1 week, whereas in the second phase a non-fluoride toothpaste (NFT) was used. The urine was collected in a 24-h period in each week-phase according to Marthaler's protocol. The urinary fluoride excretion data expressed as mean (SD) in ì g/24 h were: G1-FT= 452.9 (290.2); G1-NFT= 435.1 (187.0); G2-FT= 451.4 (224.0); G2-NFT= 430.3 (352.5); G3-FT=592.3 (390.5); and G3-NFT=623.6 (408.7). There was no statistically significant difference between the water fluoride groups, and regardless of the week phase (ANOVA, p>0.05). The use of fluoride toothpaste (1,510 ppmF) did not promote an increase in urinary fluoride excretion. There was a trend, though not significant, as to the increase of urine fluoride concentration in relation to fluoride concentrations in the water. The excretion values suggest that some children are under risk to develop dental fluorosis and information about the appropriate use of fluoride is necessary in this area.
Keywords: Fluoride; Metabolism; Urine; anticaries agent; fluoride; toothpaste; body height; body weight; Brazil; child; drinking; female; human; male; preschool child; rural population; tooth brushing; tropic climate; urine; water supply; Body Height; Body Weight; Cariostatic Agents; Child; Child, Preschool; Drinking; Female; Fluorides; Humans; Male; Rural Population; Toothbrushing; Toothpaste; Tropical Climate; Water Supply